2010
DOI: 10.1186/1477-7525-8-133
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in relapsing remitting multiple sclerosis patients during treatment with glatiramer acetate: a prospective, observational, international, multi-centre study

Abstract: BackgroundGlatiramer acetate (GA) and interferon-beta (INFb) are first-line disease modifying drugs for relapsing remitting multiple sclerosis (RRMS). Treatment with INFb is associated with a significant increase in health-related quality of life (HR-QoL) in the first 12 months. It is not known whether HR-QoL increases during treatment with GA.Methods197 RRMS patients, 106 without and 91 with prior immunomodulation/immunosuppression, were studied for HR-QoL (Leeds Multiple Sclerosis-QoL [LMS-QoL] scale, score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 28 publications
0
55
0
1
Order By: Relevance
“…Finally, as this pilot study was not a randomized controlled trial, the control group did not have a "placebo" intervention throughout the course of 10 weeks that would equate the amount of "attention" given the two groups, raising the question of whether participation in the treatment group alone can account for the results. and aerobic exercise, [30][31][32][33] as well as cognitive-behavioral therapy, 34 can reduce fatigue in MS. These interventions were not part of the psychoeducational wellness program described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as this pilot study was not a randomized controlled trial, the control group did not have a "placebo" intervention throughout the course of 10 weeks that would equate the amount of "attention" given the two groups, raising the question of whether participation in the treatment group alone can account for the results. and aerobic exercise, [30][31][32][33] as well as cognitive-behavioral therapy, 34 can reduce fatigue in MS. These interventions were not part of the psychoeducational wellness program described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A significant impact of the treatment with GA on health-related quality of life has also been reported [77,78], with beneficial effects including significant reductions in fatigue and in days of absence from work.…”
Section: Once-daily Formulation In Relapsing-remitting Multiple Sclermentioning
confidence: 97%
“…The introduction of DMTs has led to reductions in disease activity [1][2][3][4][5] and improvements in quality of life 21,22 for people with MS. We compared treatment satisfaction ratings in RRMS patients treated with IFNβ-1a IM, IFNβ-1a SC, GA, and NTZ and found no differences in overall treatment satisfaction across therapies. Participants reported that they were confident that taking the medication was a good thing for them and that they were certain that the good things about the medication outweighed the bad things.…”
Section: Discussionmentioning
confidence: 99%